P24 Visualization of intracranial aneurysms treated with Woven EndoBridge (WEB) devices using Ultrashort Echo Time Magnetic Resonance Imaging (UTE-MRI). (29th August 2022) - Toth, D; Sommer, S; Barnaure, I; Madjidyar, J; Thurner, P; Kulcsar, Z; Schubert, T
Abstract : Introduction/aim: Assessing treatment success of intracranial aneurysms with Woven EndoBridge (WEB) devices using MRI is important in follow-up imaging. Depicting both the device conformation as well as any reperfusion is challenging due to susceptibility artefacts. We demonstrate the usefulness of contrast-enhanced 3D-Ultrashort Echo-Time (UTE) sequence in this setting. Materials and methods: 21 MRIs performed after WEB treatment, in 11 patients (8 females) with a total of 13 treated aneurysms (6 anterior communicating, 5 basilar, 2 medial cerebral arteries) were prospectively included. All MRIs were performed on the same 3-Tesla scanner. Two MRIs in one patient were excluded, due to additional surgical clipping. We compared the visualization of device configuration and reperfusion in 3D isotropic UTE-MRI post contrast (TR: 4.62, TE 0.04ms) with standard time-of-flight (TOF) angiography without and with intravenous contrast, as well as DSA (available in 17/19 cases). Two interventional radiologists rated the images separately and in consensus. Results: Visualization of the WEB device position and conformation was rated as superior or highly superior using the UTE sequence in 18/19 MRIs and equal in 1, compared to TOF. Reperfusion was visible in 7/17 cases in DSA. TOF was able to grade reperfusion correctly in 13 cases and UTE in all 17 cases. Of the two remaining cases without DSA correlation, one demonstrated neck reperfusion on UTE, but not on TOF. Conclusion: Contrast-enhanced UTE is a novel MRI sequence that shows added value to standard sequences in non-invasive and radiation-free follow-up imaging of intracranial aneurysms treated using a WEB device. References: Katsuki M, Narita N, Ishida N, et al . Usefulness of 3 Tesla Ultrashort Echo Time Magnetic Resonance Angiography (Ute-Mra, Silent-Mra) for Evaluation of the Mother Vessel after Cerebral Aneurysm Clipping: Case Series of 19 Patients. Neurol Med Chir (Tokyo). 2021 Mar 15;61 (3):193–203. DOI: 10.2176/NMC.OA.2020-0336. EPUB 2021 Jan 27. PMID: 33504734; PMCID: PMC7966203. Do you have any conflict of interest to declare? : No